Positive mental health in young people in care: Findings from a new measure - Miller, Meagan; Michael, Erik; Flynn, Robert; Keyes, Corey (Université d'Ottawa | University of Ottawa, 2012)
A growing emphasis on resilience and positive youth development in child welfare makes the assessment of the positive mental health of young people in care especially timely. The present paper will provide an overview of the main findings derived from the use of Keyes’ (2006) new 14-item self-report measure of positive mental health in a cross-sectional sample of 3,954 young people aged 10-17 years and residing in out-of-home care in Ontario, Canada, in 2010-2011. Keyes’ instrument is an integral component of the revised Canadian version of the Assessment and Action Record (Flynn, Miller, Desjardins, Ghazal, & Legault, 2010) that is used in the Ontario Looking After Children (OnLAC) service-planning and outcome-monitoring project. The 14 items cover three aspects of subjective well-being: emotional (3 items), social (5 items), and psychological (6 items). We will describe the prevalence in young people in care of Keyes’ (2006) three levels of youth mental health, namely, flourishing, moderately mentally healthy, and languishing, and compare the results to the norms established by him in a large national sample of youth in the USA. We will also describe the degree of association between the positive mental health of the young people in care and other aspects of their functioning, both positive (e.g., developmental assets, pro-social behaviour, positive experiences in care, school performance) and negative (e.g., behavioural difficulties, use of drugs). The implications of the findings for the potentially wider use in child welfare of Keyes’ (2006) measure of positive mental health will be discussed. Presented at EUSARF 2012 in Glasgow, Scotland
Keywords: child welfare; positive mental health; ontario looking after children; onlac; child development